Learning and organising for radical change: A counter-history of reading groups as popular education (Journal of Applied Learning and Teaching, 2021)
Historically, radical politics has attempted both institutional and wider social change using organisation as the main method. This article uses this premise to examine examples of reading groups in relation to social and political movements. In particular it looks at the pedagogical and organisational processes that constitute reading groups and how these processes intersect with each other. This is to understand processes of organisation and processes of learning as being in parallel and directly relating to each other. While reading groups often play a minor role in social and political movements, they nonetheless can be significant. This article argues that reading groups can under some conditions and in certain contexts, contribute to the building of solidarity and provide forms of continuity or social infrastructure, in a way that other forms of organisation, such as meetings cannot. The aim here is to examine the potential for development of political agency and solidarity through self-organised study groups. By exploring these little examined group learning practices in different contexts, it might be possible to glean the potential for mutual learning and organising to help to build and sustain social infrastructures for social transformation.